The Influence of Current Ratio, Quick Ratio and Net Profit Margin on Return on Assets at PT. Hero Supermarket Tbk - Muliahadi Tumanggor (PINISI Discretion Review, 2020)
The role of finance in a company is very important and is needed both in large and small companies, both private and state-owned companies. This study aims to determine the effect of the current ratio, quick ratio and net profit margin on return on assets at PT. Hero Supermarket Tbk 2014-2018 period. The method used is explanatory research with a sample of as many financial statements. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the current ratio does not significantly influence the return on assets of 1.5%, the hypothesis test obtained significance 0.817> 0.05. The quick ratio does not significantly influence the return on assets of 30.3%, the hypothesis test obtained significance of 0.258> 0.05. Net profit margin has a significant effect on the Return on assets of 97.6%, the hypothesis test obtained a significance of 0,000 <0.05. The current ratio, quick ratio, and net profit margin simultaneously have a significant effect on the Return on assets of 99.8%, the hypothesis test obtained significance of 0.003 <0.05.